1981
DOI: 10.1042/bj2000099
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Ca2+ and Na+ across the chromaffin-granule membrane

Abstract: Bovine chromaffin-granule ghosts accumulate 45Ca2+ in a temperature- and osmotic-shock-sensitive process; the uptake is saturable, with Km 38 microM and Vmax. 28 nmol/min per mg at 37 degrees C. Entry occurs by exchange with Ca2+ bound to the inner surface of the membrane. It is inhibited non-competitively by Na+, La3+ and Ruthenium Red (Ki 10.7 mM, 7 microM and 2 microM respectively), and competitively by Mg2+ (ki 0.9 mM). Uptake was not stimulated by ATP. Na+ induces Ca2+ efflux; Ca2+ can re-enter the ghosts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
1

Year Published

1982
1982
1991
1991

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 39 publications
7
40
1
Order By: Relevance
“…Similar problems have arisen previously when secretory vesicle ghosts were used to investigate Ca2+ transport across the vesicle membrane [16]. Addition of EGTA to this preparation resulted in an instantaneous leakage of Ca2+ from the vesicles, which was only slightly modified by Na + or K +.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Similar problems have arisen previously when secretory vesicle ghosts were used to investigate Ca2+ transport across the vesicle membrane [16]. Addition of EGTA to this preparation resulted in an instantaneous leakage of Ca2+ from the vesicles, which was only slightly modified by Na + or K +.…”
Section: Discussionsupporting
confidence: 52%
“…In this context it is interesting to note that the data concerning the effect of Na + on the inhibition of Ca2+ uptake by intact secretory vesicles (see Results) are compatible with an exchange of two Na+ for one Ca2+ across the vesicular membrane. It has been reported that Ca2+ -Ca2+ exchange across the vesicular membrane is inhibited 'by Mg 2+ and Ruthenium red [16]. Since we did not find an effect of both substances on Ca2+ uptake, Ca2+ -Ca2+ exchange does not contribute significently to the uptake of Ca2+ by intact secretory vesicles which results in a net increase of intravesicular Ca2+ [I].…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The presence of a Ca2+-dependent Ca2+ efflux system was first observed with chromaffin secretory vesicle ghosts (Phillips, 1981).…”
Section: Influence Of Divalent Cations On Ca2+ Transportmentioning
confidence: 92%
“…The data are in accordance with an exchange system of 1 Ca2+ to 2 Na+ (KriegerBrauer and Gratzl, 1982). Investigations with chromaffin secretory vesicle ghosts provided evidence that in addition to the Na+/Ca2+ exchange, a Ca2+/Ca2+ exchange system exists within its membrane (Phillips, 1981). Since Na+-dependent Ca2+ uptake could also be demonstrated in the membrane of secretory vesicles from neurohypophysis (Saermark et al, 1982), such transport systems seem to be of general importance for the Ca2+ metabolism of secretory cells.…”
mentioning
confidence: 99%